90.0k views
5 votes
Substitute method 9x -2y = 3 3x -6 = y

2 Answers

5 votes

Answer:


\large\boxed{x=-3\ \text{and}\ y=-15\to(-3,\ -15)}

Explanation:


\left\{\begin{array}{ccc}9x-2y=3&(1)\\3x-6=y&(2)\end{array}\right\\\\\text{Substitute (2) to (1):}\\\\9x-2(3x-6)=3\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\9x-2(3x)-2(-6)=3\\\\9x-6x+12=3\qquad\text{subtract 12 from both sides}\\\\3x=-9\qquad\text{divide both sides by 3}\\\\\boxed{x=-3}\\\\\text{Put the value of x to (2):}\\\\y=3(-3)-6\\\\y=-9-6\\\\\boxed{y=-15}

User Yuvi
by
5.5k points
1 vote

Answer:

x = -3

y = -15

Explanation:

9x - 2y = 3

3x - 6 = y

Since the equation 3x - 6 is equal to y then you can plug in that equation in the other equation.

9x - 2(3x - 6) = 3

Solve for x

9x - 2(3x - 6) = 3

9x - 6x + 12 = 3

3x + 12 =3

3x = -9

x = -3

Now plug in x to find y

3(-3) -6 = y

-9 - 6 = y

-15 = y

plug it back in to double check your answer

9(-3) - 2(-15) = 3

-27 + 30 =3

3 = 3

hope this helps

User Cumul
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.